Natural remanent magnetization data from IODP Hole 386-M0089C - Strasser, Michael; Ikehara, Ken; Everest, Jeremy D; Maeda, Lena; Hochmuth, Katharina; Grant, Hannah; Stewart, Margaret S; Sakurai, Noriaki; Yokoyama, Takahiro; Bao, Rui; Bellanova, Piero; Brunet, Morgane; et al. (PANGAEA, 2025)
Natural remanent magnetization (NRM) data from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). The offshore phase of this expedition took place between 2021-04-13 and 2021-06-01 onboard Japanese R/V Kaimei from and to Yokosuka, Japan, followed by an onshore phase onboard D/V Chikyu between 2022-02-14 – 2022-03-15. Because the diameter of the split section (12.5 cm) is larger than the magnetometer entrance (8.1 cm), U-channel samples were taken from the center of each working half during the onshore phase. Measurements were conducted likewise during the onshore phase using the long-core superconducting rock magnetometer (2G Enterprises, model 760) installed on D/V Chikyu. Due to time constraints paleomagnetism measurements were limited to NRM with 5 mT demagnetization, with measurements typically made at 2 cm intervals. Because linearity is difficult to calculate for short cores, such as trigger cores, corrections of declination were not performed for these cores. For further methodological information see methods chapter in Strasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023
Keywords: International Ocean Discovery Program (IODP); IODP; Japan Trench; Paleomagnetic data